2020
DOI: 10.18502/acta.v57i10.3247
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Physical Activity in Iranian Dyslipidemic Patients

Abstract: Dyslipidemia is an important cause of cardiovascular diseases with increasing rates among adult populations. Nutrition and physical activity are known to have an impact on degrees of dyslipidemia. In this article, we had a study on nutritional behaviors and physical activities among middle-aged adults with and without dyslipidemia. In this case-control study, 200 middle-aged adults were entered. One hundred adults with dyslipidemia and 100 normal adults were included in this study. Data regarding desirable or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…Quite interestingly, the marital status affected the distribution of DL in our sample, with the widowed patients holding the lion’s share, as also proved in the research of Nikparvar et al (2020) 37 . Additionally, our results demonstrated that factors such as ex-smoking, obesity, sedentary life, and unhealthy diets may contribute to higher DL rates of developing populations, along with previous studies 38 , 39 . Finally, in keeping with our results emerging evidence from the study of Rekleiti et al (2012) 40 demonstrated the independence of DL as a prognostic factor for anxiety.…”
Section: Discussionsupporting
confidence: 85%
“…Quite interestingly, the marital status affected the distribution of DL in our sample, with the widowed patients holding the lion’s share, as also proved in the research of Nikparvar et al (2020) 37 . Additionally, our results demonstrated that factors such as ex-smoking, obesity, sedentary life, and unhealthy diets may contribute to higher DL rates of developing populations, along with previous studies 38 , 39 . Finally, in keeping with our results emerging evidence from the study of Rekleiti et al (2012) 40 demonstrated the independence of DL as a prognostic factor for anxiety.…”
Section: Discussionsupporting
confidence: 85%
“…This finding has been shown in some studies in Iran. So that individuals with dyslipidemia tend to have lower levels of physical activity compared to those without dyslipidemia 20,21 . Several studies have shown that physical activity can help reduce the risk of dyslipidemia by promoting weight loss 22 , increasing HDL cholesterol levels 23 , lowering LDL cholesterol levels 23 , and improving insulin sensitivity 24 .…”
Section: Discussionmentioning
confidence: 99%